Sensing technologies for measuring grain loss during harvest in paddy field: a review - Bomoi, Muhammad Isa; Mat Nawi, Nazmi; Abd Aziz, Samsuzana; Mohd Kassim, Muhamad Saufi (Multidisciplinary Digital Publishing Institute, 2022)
first_pageDownload PDFsettingsOrder Article Reprints Open AccessReview Sensing Technologies for Measuring Grain Loss during Harvest in Paddy Field: A Review by Muhammad Isa Bomoi 1,2,*ORCID,Nazmi Mat Nawi 1,3,4ORCID,Samsuzana Abd Aziz 1,3 andMuhamad Saufi Mohd Kassim 1,3,4 1 Department of Biological and Agricultural Engineering, Faculty of Engineering, University Putra Malaysia (UPM), Serdang 43400, Malaysia 2 Scientific Equipment Development Institute, Minna 920001, Nigeria 3 SMART Farming Technology Research Centre, Faculty of Engineering, University Putra Malaysia (UPM), Serdang 43400, Malaysia 4 Institute of Plantation Studies, University Putra Malaysia (UPM), Serdang 43400, Malaysia * Author to whom correspondence should be addressed. AgriEngineering 2022, 4(1), 292-310; https://doi.org/10.3390/agriengineering4010020 Received: 29 January 2022 / Revised: 13 February 2022 / Accepted: 1 March 2022 / Published: 9 March 2022 Downloadkeyboard_arrow_down Browse Figures Review Reports Versions Notes Abstract A combine harvester has been widely employed for harvesting paddy in Malaysia. However, it is one of the most challenging machines to operate when harvesting grain crops. Improper handling of a combine harvester can lead to a significant amount of grain loss. Any losses during the harvesting process would result in less income for the farmers. Grain loss sensing technology is automated, remote, and prospective. It can help reduce grain losses by increasing harvesting precision, reliability, and productivity. Monitoring and generating real-time sensor data can provide effective combine harvester performance and information that will aid in analyzing and optimizing the harvesting process. Thus, this paper presents an overview of the conventional methods of grain loss measurements, the factors that contribute to grain losses, and further reviews the development and operation of sensor components for monitoring grain loss during harvest. The potential and limitations of the present grain loss monitoring systems used in combine harvesting operations are also critically analyzed. Several strategies for the adoption of the technology in Malaysia are also highlighted. The use of this technology in future harvesting methods is promising as it could lead to an increase in production, yield, and self-sufficiency to meet the increasing demand for food globally.